Ketogenic Diet Therapy for Drug-Resistant Epilepsy and Cognitive Impairment in Children With Tuberous Sclerosis Complex - Fang, Yu; Li, Dan; Wang, Man; Zhao, Xia; Duan, Jing; Gu, Qiang; Li, Baomin; Zha, Jian; Mei, Daoqi; Bian, Guangbo; Zhang, Man; Zhang, Huiting; et al. (Frontiers in Neurology, 2022)
Objective: Cognitive impairment and epilepsy derived from tuberous sclerosis complex (TSC) severely impact children with this rare disease. Ketogenic diet (KD) therapy has been consistently reported to be beneficial to TSC patients. In the study, we aimed to investigate the efficacy and safety of the KD for cognitive impairment and drug-resistant epilepsy in children with TSC. Methods: This multicenter study retrospectively enrolled 53 children with cognitive impairment or drug-resistant epilepsy caused by TSC from 10 hospitals from January 1, 2010, to December 31, 2020. The intention-to-treat analysis was used to evaluate the outcome of development or cognition improvement and seizure reduction. Results: Overall, of 53 children with TSC, 33 patients were male and 20 were female. Among them, 51 children failed to be seizure-free with a mean of 5.0 (4 to 6) anti-seizure medications (ASMs) before KD. Although 2 patients had achieved seizure freedom before KD, they still had psychomotor development delay and abnormal electroencephalogram (EEG). After KD therapy, 38 of the 51 patients (74.5%) with psychomotor retardation had cognitive function improved. At 1, 3, 6, and 12 months after KD, there respectively remained 51 (100%), 46 (90.2%), 35 (68.6%), and 16 patients (31.4%) on the diet therapy. At the above time points, there were 26 (51.0%), 24 (47.1%), 22 (43.1%) and 13 patients (25.5%) had ≥50% reduction in seizures, including 11 (21.6%), 12 (23.5%), 9 (17.6%) and 3 patients (5.9%) with seizure free effect accordingly. During KD, no serious side effects occurred in all patients. Gastrointestinal disturbance (20 of 53, 37.7%) and hyperlipidemia (6 of 53, 11.3%) were the main side effects that were relieved by adjusting the KD ratio and by symptomatic treatment. Conclusion: KD is an effective and safe treatment for children with TSC-related cognitive impairment and drug-resistant epilepsy. KD can both improve cognition and behavior and reduce seizure frequency, but the long-term retention rate needs to be improved.